Degradation of Di- Through Hepta-Chlorobiphenyls in Clophen Oil Using Microorganisms Isolated from Long Term PCBs Contaminated Soil - Sharma, Jitendra K. (Springer India, 2014)
Present work describes microbial degradation of selected polychlorinated biphenyls (PCBs) congeners in Clophen oil which is used as transformer oil and contains high concentration of PCBs. Indigenous PCBs degrading bacteria were isolated from Clophen oil contaminated soil using enrichment culture technique. A 15 days study was carried out to assess the biodegradation potential of two bacterial cultures and their consortium for Clophen oil with a final PCBs concentration of 100 mg kg(−1). The degradation capability of the individual bacterium and the consortium towards the varying range of PCBs congeners (di- through hepta-chlorobiphenyls) was determined using GCMS. Also, dehydrogenase enzyme was estimated to assess the microbial activity. Maximum degradation was observed in treatment containing consortium that resulted in up to 97 % degradation of PCB-44 which is a tetra chlorinated biphenyl whereas, hexa chlorinated biphenyl congener (PCB-153) was degraded up to 90 % by the consortium. This indicates that the degradation capability of microbial consortium was significantly higher than that of individual cultures. Furthermore, the results suggest that for degradation of lower as well as higher chlorinated PCB congeners; a microbial consortium is required rather than individual cultures.